1993
DOI: 10.1111/j.1365-3024.1993.tb00587.x
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine development against cutaneous leishmaniasis. Subcutaneous administration of radioattenuated parasites protects CBA mice against virulent Leishmania major challenge

Abstract: Experiments described in this paper were aimed at determining whether subcutaneous inoculation of live, avirulent Leishmania major would protect mice against infection by the virulent parasite. To this effect, promastigotes or amastigotes of a highly virulent strain of L. major (MRHO/IR/76), used in human trials of leishmanization, and which induces non-healing skin lesions in both CBA and BALB/c mice, were rendered non-pathogenic by gamma irradiation. A dose of 150 krad was required to abrogate the virulence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
0
5

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 16 publications
2
49
0
5
Order By: Relevance
“…The isolation of L. major or L. panamensis from the healed lesions of hamsters is consistent with previous observations regarding parasite persistence concomitant with a partially effective immune response, both in humans and laboratory animals (Rivier et al 1993, Aebischer 1994. It is worth noting that in our experiment no L. major could be detected in the animals that received a single injection of live promastigotes, and were unprotected upon challenge with L. panamensis.…”
Section: Discussionsupporting
confidence: 92%
“…The isolation of L. major or L. panamensis from the healed lesions of hamsters is consistent with previous observations regarding parasite persistence concomitant with a partially effective immune response, both in humans and laboratory animals (Rivier et al 1993, Aebischer 1994. It is worth noting that in our experiment no L. major could be detected in the animals that received a single injection of live promastigotes, and were unprotected upon challenge with L. panamensis.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have shown that BALB/c mice injected with avirulent or with irradiated parasites were also protected from infection (24,25). In mouse, L. major parasites lacking the gene encoding the enzyme dihydrofolate reductase-thymidylate synthetase (DHFR-TS) induced protection against infection with either L. major or L. amazonensis (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, because of the small load of antigen delivered by the transient challenge, the immune responses may be skewed even more towards a ThI-type than in natural infections (30,31). Such immunisation will also deliver many more parasite antigens than the limited number possible with recombinant or sub-unit antigens (25).…”
Section: Discussionmentioning
confidence: 99%
“…La siguiente vía en el desarrollo de vacunas contra Leishmania fue el uso de parásitos vivos atenuados por medios físicos, químicos o genéticos, a saber: cultivos in vitro por largos períodos, sensibilidad a la temperatura, atenuación por rayos gamma, atenuación química, mutagénesis química, cultivos bajo presión de drogas y modificaciones del parásito como la disrupción genética (46)(47)(48)(49)(50). Sin embargo, los principales problemas del uso de parásitos atenuados son la seguridad y la poca factibilidad de utilizarlos a gran escala en el campo (42,51).…”
Section: Segunda Generación De Vacunasunclassified
“…Por esta razón, actualmente se está investigando con la radiación ionizante en la atenuación de Leishmania para el desarrollo de vacunas, empleando para ello el modelo del ratón BALB/c y las vías de administración intramuscular e intraperitoneal (49,75).…”
Section: Segunda Generación De Vacunasunclassified